Occupational outlook handbook 2024 (Bernan Press, 2024)
"The Occupational Outlook Handbook (OOH) is the premier, nationally recognized source for career information. Especially designed to provide valuable up-to-date information, the Handbook is great for all individuals making decisions about their future including students about to graduate from high school or college, recent graduates, individuals returning to the workforce after an absence, or anyone looking for a career change. It has been used by millions since the 1940s. The completely updated OOH reflects employment information released in September 2022. It includes information on the fastest-growing occupations, number of new jobs, and a summary of the highest-paying occupations."--